Labour issues in the context of economic integration and free trade : a Caribbean perspective - Momm, Willi (ILO Caribbean Office Port of SpainTT, 1999)
Seeks to generate awareness about the importance of developing labour market responses to globalization and hemispheric integration. Addressess two principal issues: how can labour policy facilitate the transition from protected to open economies; and, what is the likely impact of the dynamics of globalization and economic integration on Caribbean labour markets and their instituttions.